2021
DOI: 10.25165/j.ijabe.20211401.5967
|View full text |Cite
|
Sign up to set email alerts
|

Preservative effects of the combined treatment of slightly acidic electrolyzed water and ice on pomfret

Abstract: This study assessed the combined effect of slightly acidic electrolyzed water (SAEW) and slightly acidic electrolyzed water ice (SAEW-ice) on the quality of pomfrets over a period of 18 d of cold storage at 4°C. A presoak for 5 min in SAEW solution (22 mg/L) was used before the pomfrets were placed on SAEW-ice (pH: 6.45; ORP: 803 mV; ACC: 18 mg/L); The changes in physicochemical properties (i.e., pH, thiobarbituric acid, total volatile basic nitrogen and texture profile), microbial loads and sensory characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…Huang et al . (2021) also demonstrated that the initial TVC in pomfret was significantly reduced and exceeded the corruption limit at day 12 by SAEW treatment, due to the SAEW‐ice induced an effective delay in bacterial growth. Gao et al .…”
Section: Resultsmentioning
confidence: 93%
“…Huang et al . (2021) also demonstrated that the initial TVC in pomfret was significantly reduced and exceeded the corruption limit at day 12 by SAEW treatment, due to the SAEW‐ice induced an effective delay in bacterial growth. Gao et al .…”
Section: Resultsmentioning
confidence: 93%
“…As a thawing medium, SAEW could better ensure the thawed beef quality and delay lipid and protein oxidation [16] . Moreover, SAEW and SAEW ice had a positive influence on maintaining the quality and shelf life of pomfret [17] .…”
Section: Introductionmentioning
confidence: 98%
“…Recently, due to the slightly acidic pH and low available chlorine concentration (ACC, 60–100 mg/L), slightly acidic electrolyzed water (SAEW) has been used as a disinfectant in food industry and it has no adverse influence on the appearance of fish (Yan et al., 2020). SAEW contains the main bactericidal component hypochlorite produced by electrolysis of a certain concentration of electrolytes such as sodium chloride and dilute hydrochloric acid (Huang et al., 2021). Moreover, previous research showed that SAEW exhibited an equivalent or stronger antimicrobial ability than acidic electrolyzed water and can kill natural microbiota on the surface of food (Huang et al., 2021 and Mansur et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SAEW contains the main bactericidal component hypochlorite produced by electrolysis of a certain concentration of electrolytes such as sodium chloride and dilute hydrochloric acid (Huang et al., 2021). Moreover, previous research showed that SAEW exhibited an equivalent or stronger antimicrobial ability than acidic electrolyzed water and can kill natural microbiota on the surface of food (Huang et al., 2021 and Mansur et al., 2015). Liu et al (2021) found that the SAEW and slurry ice treatment had a strong inhibitory effect on microbial growth and could extend the shelf‐life of Pneumatophorus japonicus .…”
Section: Introductionmentioning
confidence: 99%